Monoclonal antibodies blocking CGRP for prevention of migraine - Alicja Maziarczyk; Dominika Miazga; Laura Surdacka (Kazimierz Wielki University, 2023)
Introduction and purpose Monoclonal antibodies blocking calcitonin gene-related peptide (CGRP) are a novel treatment strategy developed specifically for prevention of migraine. Four drugs belong to this group: eptinezumab, fremanezumab and galcanezumab, which bind to the peptide; and erenumab, which blocks the CGRP receptor. CGRP is involved in nociception and plays a crucial role in the pathophysiology of migraine, as it is released in the trigeminal ganglion as a response to local cerebral vasoconstriction in order to cause dilation of the vessels and maintain cerebral blood flow. Moreover, administration of CGRP, especially among migraineurs, induces a migraine-type headache. The aim of the paper is to discuss the potential of monoclonal antibodies blocking CGRP for the prevention of migraine and to outline their safety and efficacy profile. State of knowledge Several randomised clinical trials have shown a significant efficacy of these drugs compared to placebo in reducing monthly migraine affected days, among patients suffering from both episodic and chronic migraine. Incidence rate of side effects is low; the most common were mild to moderate (e.g. pain at the injection site, upper respiratory tract infections, nasopharyngitis, back pain and urinary tract infection). Anti-CGRP monoclonal antibodies exhibit a superior benefit-to-risk ratio than established preventive treatments. Conclusions Randomized controlled trials are still needed in order to compare different anti-CGRP monoclonal antibodies and asses their long-term safety profile. In conclusion, these drugs seem to provide promising prospects of improving the lives of migraineurs. As based on current knowledge, the benefits are superior to the likelihood of harm.